Impacto do coco híbrido na produção rural do Ceará - Moura, Nicole Sarah Carvalho Ponte (2024)
Coconut cultivation is concentrated in many countries to meet the growing demand for byproducts. Brazil is the fifth largest producer and who has the highest yield (13,114 kg/ha in 2020 and 12,588 kg/ha in 2021), due to relevant factors such as techno-Logia used in the culture, conduction and management of coconut trees, besides the use of improved dwarf and hybrid varieties. Thus, the present study has as main objective Ava-Liar the impact of hybrid coconut BRS 001 on the production of farmers in the state of Ceará. The data used were obtained through a semi-structured questionnaire of rural producers in the municipalities of Acaraú, Marco, Itarema, Amontada, Paraipaba and Trairi. Then, the method of balancing by entropy was applied to obtain the main results. Descriptive statistics show that 80% of respondents own the land in which they produce and 22% of producers said they have active debt and 14% are associated or cooperated. As for the technology used, the average amount of machinery and implements is 2 per property and 9 employees on average. From this perspective, about 59% of producers have some kind of technical assistance. The results of the parea-mento conclude that the choice of the analyzed producers in planting the dwarf variety, acres-centou 32,463 fruits per hectare/year. In contrast, it was found that the hybrid coconut BRS 001 increased the producer’s revenue by R$ 2,543.30 per hectare, due to the higher price of dry coconut in 2022. The coconut production chain is considered of great importance eco-nomic and social due to the wide variability of products and co-products that can be obtained from fruits and other parts of the plant and the generation of jobs in the state of Ceará. Therefore, it is necessary policies that encourage cultivation and permanence, production, sustainability and competitiveness in the world market of Brazilian production.